Avaliação da imunogenicidade de epitopos de células T das proteínas Sm14 e paramiosina do schistosoma mansoni em modelo murino. - Teresa Cristina Melo Garcia (2008)
Sm14 and paramyosin are S. mansoni antigens able to induce partial protection in the murine model, and are recognized by individuals resistant to S. mansoni. Recently our group has identified Sm14 and paramyosin epitopes preferentially recognized by PBMC of S. mansoni resistant individuals [Sm14 (32-48), Sm14 (53-69), Para (6-22), Para (210-226), Para (355-371)]. In order to investigate the protective potential of these synthetic epitopes peptide-based vaccines formulations were prepared using a mixture of Sm14 and paramyosin peptides or Sm14 or paramyosin separately. Immunization of mice with peptide total mixture or Sm14 peptides were able to induce a Th1 type of immune response, that was associated respectively with a significant reduction on worm burden [(29%; 28%) and (26%; 36.7%)]; reduction in the number of viable eggs/female worms (46% and 67%); reduction in the number of granuloma (52% an 61%) and granuloma area (43% and 54%). On the other hand, paramyosin peptide immunization did not engender protective immunity or pathology reduction and it was associated with a Th2 type of immune response. Since eggs in host tissues are the major cause of pathology, and schistosomes do not replicate within their mammalian hosts, an anti-fecundity vaccine, could decrease human pathology and disease transmission. Here we observed that immunization with Sm14 T cell epitopes previous recognized by resistant individuals seems to be able to induce reduction in fecundity and pathology, and therefore are potential candidates to compose a subunit vaccine against schistosomiasis.